Comparative effect of ARNI and ACEI/ARB on left ventricular diastolic function in patients with hypertensive heart disease - YANG Hao; HE Yi; WANG Fangjuan (陆军军医大学学报)
Objective‍　‍To investigate whether there exist differences in the improvement of left ventricular diastolic function between angiotensin receptor-neprilysin inhibitor (ARNI) and angiotensin-converting enzyme inhibitor (ACEI)/angiotensin receptor blocker (ARB) in patients with hypertensive heart disease (HHD). Methods‍　‍A retrospective cohort study was conducted on the HHD patients admitted in Department of Cardiovascular Diseases of our hospital from January 2021 to December 2024. The general information, echocardiographic parameters before and after treatment, and results of routine tests were collected. Finally, 517 HHD patients were subjected, including 117 receiving ARNI treatment (ARNI group) and 400 getting ACEI/ARB treatment (ACEI/ARB group). A 1∶1 propensity score matching (PSM) was performed with a caliper value of 0.02, resulting in 89 matched cases for each group. Electrocardiography was performed to assess left ventricular diastolic dysfunction (LVDD), with various parameters, including left atrial volume index, early diastolic peak velocity at the interventricular septal portion of mitral annulus (septal e’), early diastolic peak velocity at the lateral wall portion of mitral annulus (lateral e’), tricuspid regurgitation velocity, and E/e’. These parameters were followed up and reassessed during the treatment period. Kaplan-Meier survival curve was plotted to compare the incidence of LVDD between the 2 groups. Multivariable logistic regression model was employed to identify the risk factors contributing to LVDD. Results‍　‍The median follow-up time was 412 (309, 736) d in the whole cohort, and was 409 (300, 729) d for the patients after PSM. Kaplan-Meier survival analysis demonstrated that the incidence of LVDD was lower in the ARNI group than the ACEI/ARB group both before and after PSM (P<0.05). After treatment, the ARNI group obtained lower lateral e’ [8.00 (7.00, 9.40) vs 9.00 (7.10, 10.30) cm/s, P<0.001], thinner left ventricular posterior wall thickness [12.20 (10.80, 12.80) vs 12.30 (11.20, 12.90) mm, P<0.048] when compared with the ACEI/ARB group. After adjusting for confounding factors, multivariable logistic regression analysis revealed that advanced age (OR=1.082, P<0.001), increased systolic blood pressure (OR=1.009, P=0.005), thicker left ventricular posterior wall thickness (OR=1.462, P<0.001), left atrial enlargement (OR=1.081, P<0.001), and use of calcium channel blocker (OR=1.548, P=0.006) were independent risk factors for LVDD, and positively correlated with the risk of LVDD. While, male (OR=0.709, P=0.043) and BMI (OR=0.933, P=0.006) were protective factors, which were negatively correlated with LVDD risk. Conclusion‍　‍In HHD patients, ARNI is superior to ACEI/ARB in reducing the incidence of LVDD.